Pioglitazone Ameliorates Intracerebral Insulin Resistance and Tau-protein Hyperphosphorylation in Rats with Type 2 Diabetes - Hu, S.-H.; Jiang, T.; Yang, S.-S.; Yang, Y. (Experimental and Clinical Endocrinology & Diabetes, 2013)
To investigate intracerebral insulin resistance and its relationship with tau-protein hyperphosphorylation.A rat model of type 2 diabetes (T2D) was established with streptozotocin (STZ). Diabetic rats received intragastric administration of pioglitazone (PIO group) or normal saline (T2D group) for 4 weeks. As a control, non-diabetic rats received intragastric normal saline (CTL group). The insulin concentrations in cerebrospinal fluid (CSF) and blood were determined with radioimmunoassay, and blood glucose concentration was determined using a glucose oxidation technique. Total and phosphorylated levels of protein kinase B (AKT), glycogen synthase kinase-3β (GSK-3β) and tau-protein in the hippocampus were analyzed using western blotting.The plasma insulin level in the T2D group was higher, and the CSF insulin level in the T2D group lower than in the CTL group. Hippocampal phosphorylated AKT and phosphorylated GSK-3β levels were significantly lower in the T2D group than in the CTL group. Hippocampal tau-protein in the T2D group was hyperphosphorylated at Ser199 and Ser396. Plasma insulin levels in the PIO group were lower than in the T2D group, with no differences in CSF insulin levels. Phosphorylated AKT and phosphorylated GSK-3β levels in the PIO group were significantly higher than in the T2D group. Hippocampal phosphorylated tau-protein (Ser199/Ser396) was lower in the PIO group than in the T2D group.Hyperphosphorylation of tau-protein in pioglitazone-treated rats with T2D was improved. Rats with T2D have both cerebral insulin resistance and cerebral hypoinsulinism. Pioglitazone can ameliorate intracerebral insulin resistance and decrease tau-protein hyperphosphorylation, but cannot increase intracerebral insulin levels.
Keywords: Alzheimer’s disease; dementia; glucose metabolism; anti-diabetic drug